Current and emerging strategies to combat antimalarial resistance. Issue 3 (4th March 2022) - Rasmussen, Charlotte; Alonso, Pedro; Ringwald, Pascal
ABSTRACT: Introduction: Since the spread of chloroquine resistance in Plasmodium falciparum in the 1960s, recommendations have been made on how to respond to antimalarial resistance. Only with the advent of artemisinin partial resistance were large-scale efforts made in the Greater Mekong Subregion to carry out recommendations in a coordinated and well-funded manner. Independent emergence of parasites partially resistant to artemisinins has now been reported in Rwanda. Areas covered: We reviewed past recommendations and activities to respond to resistance as well as ongoing research into new ways to stop or delay the spread of resistant parasites. Expert opinion: Inadequate information limits the options and support for a strong, coordinated response to artemisinin partial resistance in Africa, making better phenotypic and genotypic surveillance a priority. A response to resistance needs to address factors that may have hastened the emergence and could speed the spread, including overuse of drugs and lack of access to quality treatment. New ways to use the existing treatments in response to resistance, such as multiple first-lines, are currently impeded by the limited number of drugs available.